THE EFFECT OF AGREEABLENESS ON INNOVATIVE BEHAVIOR IN MILLENNIAL GENERATION EMPLOYEES IN THE SPECIAL REGION OF YOGYAKARTA WITH KNOWLEDGE SHARING AS AN INTERVENING VARIABLE - Fita Sari; Nur Wening (International Journal of Business, Law and Political Science, 2024)
The success of a company cannot be separated from the role of its human resources. In this era of digitalization and increasingly rapid technological developments, companies are required to always innovate. This research will examine the influence of agreeableness on innovative behavior with knowledge sharing as an intervening variable. Sampling in this study used purposive sampling technique with 60 respondents with the criteria of millennial generation employees aged 27-42 years who live and work in the Special Region of Yogyakarta. The tests carried out in this research were instrument testing (validity test and reliability test), classical assumption test, hypothesis test (t test), coefficient of determination and path analysis using the Sobel test. The results of this research show that agreeableness has a positive and significant effect on knowledge sharing, knowledge sharing has a positive and significant effect on innovative behavior, agreeableness has a positive and significant effect on innovative behavior and knowledge sharing partially mediates the influence of agreeableness on innovative behavior.